Cockfighting as an Alternative Economic Solution for the People of Tuyun Village, Mihing Raya District, Gunung Mas Regency - Pitoyo, Dhanu; Firmanto, Firmanto (Budapest International Research and Critics University, 2020)
This study aims to analyze alternative solutions for villagers' denominations of cockfighting games in Tuyun Village, Mihing Raya District, Gunung Mas Regency. The research method used is descriptive qualitative research methods. The subjects of this study are people who play a role in cockfighting, namely gold miners who play cockfighting games and rooster sellers. Data collection techniques through interviews, observation and documentation. The results of this study indicate that people who play cockfighting because they cannot work to mine gold in the dry season, so they spend their time playing cockfighting, in addition to providing income for small traders who sell around the cockfighting arena.